Role of glomerular filtration rate‐modifying drugs in the development of anticoagulant‐related nephropathy. Issue 1 (11th January 2021) - Medipally, Ajay K.; Xiao, Min; Rovin, Brad H.; Satoskar, Anjali A.; Ivanov, Iouri; Qaisar, Shahzeb; Brodsky, Sergey V.
Abstract: Introduction: Anticoagulant‐related nephropathy (ARN), that was described in humans first as warfarin‐related nephropathy, is characterized by acute kidney injury and red blood cell (RBC) tubular casts in the kidney. 5/6 nephrectomy (5/7NE) rats treated with warfarin or dabigatran show changes in kidney function and morphology that are similar to human disease. The role of glomerular filtration rate (GFR) in the pathogenesis of ARN is not clear. The aim of these studies was to elucidate the role of GFR in the pathogenesis of dabigatran‐induced ARN in 5/6NE rats. Methods: 5/6NE rats were treated per os with 150 mg/kg/day dabigatran alone or with drugs that lower (enalapril, 1.5 mg/kg/day) or increase (albuterol, 4.0 mg/kg/day) GFR for 7 days. Changes in coagulation and kidney function were recorded daily. Kidney morphology was evaluated on day 7 after the treatment. Results: Dabigatran resulted in activated partial thromboplastin time increase that was not affected by GFR‐modifying drugs. Blood pressure was significantly lower in 5/6NE rats treated with enalapril and dabigatran as compared to dabigatran alone. The GFR was decreased by 35% in enalapril/dabigatran‐ and increased by 26% in albuterol/dabigatran‐treated animals. There were no changes in serum creatinine, hematuria or urinary kidney injury molecule (KIM‐1) levels when GFR‐modifying drugs were added to dabigatran. All dabigatran‐treated animals had RBC casts in the kidney regardless of the GFR modification. Conclusions: GFR does not play a significant role in the dabigatran‐induced acute kidney injury in 5/6 nephrectomy model in rats. Based in these data, modification of GFR in patients with ARN is not warranted. Abstract : Changes in the glomerular filtration rate (GFR) do not play a significant role in the development of anticoagulant‐related nephropathy (ARN), at least in the 5/6 nephrectomy rat model. Therefore, treatment with GFR‐modifying drugs does not appear to be beneficial for patients with ARN.